2015
DOI: 10.5194/soil-1-287-2015
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the recent approaches to terroir functional modelling, footprinting and zoning

Abstract: Abstract. Notions of terroir and their conceptualization through agro-environmental sciences have become popular in many parts of world. Originally developed for wine, terroir now encompasses many other crops including fruits, vegetables, cheese, olive oil, coffee, cacao and other crops, linking the uniqueness and quality of both beverages and foods to the environment where they are produced, giving the consumer a sense of place. Climate, geology, geomorphology and soil are the main environmental factors which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 253 publications
(274 reference statements)
0
75
0
3
Order By: Relevance
“…Vaudour et al (2015) reported that in the last ten years several studies have been carried out to evaluate soil erosion processes in traditional European viticulture areas of France, Spain or Italy. Numerous authors claimed that the extreme rainfall events, the steep slopes, the intensive soil tillage practices and the soil surface components could be the most relevant indicators to analyse and classify actual soil erosion processes for these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Vaudour et al (2015) reported that in the last ten years several studies have been carried out to evaluate soil erosion processes in traditional European viticulture areas of France, Spain or Italy. Numerous authors claimed that the extreme rainfall events, the steep slopes, the intensive soil tillage practices and the soil surface components could be the most relevant indicators to analyse and classify actual soil erosion processes for these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion is a problem in vineyards because it reduces soil fertility, damages nearby roads, and causes floods, Lieskovský and Kenderessy, 2014;Martínez-Casasnovas et al, 2015;Vaudour et al, 2015). Higher erosion rates have been recorded in vineyards than in other land use areas (Cerdan et al, 2010) in the Mediterranean region (Vanmaercke et al, 2011) because of several characteristics of the soil, climate, topography, soil management and the vines are planted and cultivated along the slope (Novara et al, 2011;Tarolli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All these activities notably affect one of the most important components of the terroir: the soil. Pedological process research in terroirs has become one of the most relevant topics nowadays in geosciences [10]. Vineyards are notably one of the land uses, in particular in Mediterranean environments, in which high erosion rates are being recorded [11].…”
Section: Introductionmentioning
confidence: 99%